Missense variants in the spectrin repeat domain of DSP are associated with arrhythmogenic cardiomyopathy: A family report and systematic review. Issue 10 (18th August 2020) - Grondin, Steffany; Wazirian, Avedis‐Christ; Jorda, Paloma; Terrone, Donato G.; Gagnon, Johannie; Robb, Laura; Amyot, Julie; Rivard, Lena; Pagé, Sylvain; Talajic, Mario; Cadrin‐Tourigny, Julia; Tadros, Rafik
Abstract: Rare loss of function variants in DSP, which codes for the desmosomal protein desmoplakin, have been implicated in dilated and arrhythmogenic right ventricular cardiomyopathies. We present a family with arrhythmogenic cardiomyopathy associated with a novel missense variant in DSP (NM_004415.4): c.877G>A, p.(Glu293Lys). The phenotype is characterized by predominant involvement of the left ventricle with systolic dysfunction, fibrosis, and life‐threatening arrhythmias. We performed a systematic review of literature collecting all cardiomyopathy cases with rare missense variants in DSP . We demonstrate that the distribution of missense variants across the protein domains in cardiomyopathy cases differs from that in gnomAD ( p = .04), with a case enrichment of rare missense variants in the spectrin repeat domain (36/78 [46%] in cases vs. 449/1495 [30%] in gnomAD; p = .004). Our findings highlight the predominance of cardiac arrhythmia and left ventricular involvement in desmoplakin cardiomyopathy and pinpoint to a potential mutation hotspot in DSP thereby facilitating missense variant interpretation in the diagnostic setting.